Prenatal and Postnatal Diagnosis of Intrauterine Ovarian Torsion - Elena V. Sibirskaya; Irina V. Karachentsova; Alsu R. Minazhetdinova; Mariya Yu. Chernysheva; Adelina A. Khairullina ("Paediatrician" Publishers LLC, 2023)
Intrauterine ovarian torsion is the most common complication of ovarian cysts in fetuses. This pathology is asymptomatic in the postnatal period, thus, it is difficult to diagnose especially in cases then torsion signs were not revealed before birth. This review presents the criteria used in pre- and postnatal diagnosis of ovarian torsion. The main ultrasound markers were identified, as well as the possibilities of using MRI were considered. Timely diagnosis of this pathology in prenatal period contributes to more careful examination of the child after birth. This will determine the management tactics, preserve girl's reproductive function, and avoid any complications from other organs and systems.